Examining Iranian EFL Students’ Correct Use of Tense: Connecting the Past to the Present - Abdulhay, Husain (Jurnal Pedagogy, 2024)
This study aimed to examine the ability of Iranian English as a Foreign Language (EFL) students to accurately recognize and use past, present perfect, and present perfect progressive tenses. A mixed-method approach was employed to gather both qualitative and quantitative data. The study involved 65 EFL students majoring in English language at a university in Iran, all of whom had previously taken grammar courses. The findings revealed that most students struggled to distinguish between the past tense and the present perfect or present perfect progressive tenses. In both the production and recognition tests, there were frequent instances of the past tense being incorrectly used instead of the present perfect. The analysis also highlighted errors stemming from mismatches in tense usage, particularly in reflecting the relationship between event time and speech time. Students often failed to accurately translate events that began in the past but continued to affect the present. These difficulties can be attributed to differences between the tense systems of English and Persian. Persian lacks the ability to express the continuum of time, especially the relationship between speech time and reference points that are inherent in English non-past perfect verb forms. Furthermore, students' reliance on their native language in the early stages of language acquisition led to erroneous tense transfers from Persian to English. The findings contribute to EFL programs by emphasizing the importance of addressing tense-related challenges and incorporating a deeper understanding of the differences between English and Persian tense structures.